Advantages of serological testing for Helicobacter pylori infection as a screening test - Daivasikamai, Premkumar (International Journal of Advances in Medicine, 2017)
Background: As the practicing physicians start treating all dyspeptic symptoms as peptic ulcer disease and some patients are treated for Helicobacter pylori infection without confirmation of infection. Hence, a simple and convenient test to identify the H. pylori infection is essential in the management of all dyspepsia. Serological test is a noninvasive test and result can be obtained within short time and treatment can be started early. Methods: A total of 86 outpatients with dyspeptic symptoms underwent both serological test and endoscopy and biopsy for H. pylori infection. Serological testing for H. pylori is based on the immunoglobulin G antibody to H. pylori infection. Results: Of 86 patients, 79 patients’ biopsy were positive for H. pylori and 77 patients were positive by serology. Of them, 75 were both positive for H. pylori by biopsy and also by serology. Those 7, who are negative for histology is also negative for serology. Comparing endoscopic biopsy with serology, the specificity, sensitivity are 97.5, 98 for serology. Conclusions: Serological tests assess the global presence of H. pylori in the stomach even when the bacteria are irregularly distributed on the gastric mucosa. Serology testing is cheaper and more convenient, and thus should be preferred in situations where the additional information yielded by an endoscopy is not needed.